A proposed regulatory mechanisim of ontogenetically expressed DITAA-containing coconut transcripts - Cueno, Marni E. (Philippine Journal of Science, 2013)
Accumulation of medium-chain oils into the coconut endosperm has been shown to follow a temporal pattern of fatty acid gene expression. The mechanism by which these genes are regulated, however, has not been explored. Using 3’ RACE, we identified two coconut DITAA-containing transcripts (DCTs), appropriately labeled DCT1 and DCT2, and found both transcripts in the 5-6 and 6-7 month old (mo) coconut endosperms following an ontogenetic pattern. Comparison of both amplified transcripts from the 5-6 and 6-7 mo endosperms show 100% homology between DCT2 transcripts. Interestingly, 52 nt downstream of the DCT1 sequences prior to the poly(A) tail are missing in the DCT1-6mo transcript. Visual inspection for potential motifs shows the presence of CCGCC-like (DCT1-5mo and DCT1-6mo) and TGTG-like (DCT1-6mo only) motifs. Both motifs have been published to be known regulatory motifs in other species suggesting a probable similar function in coconut.